2017
DOI: 10.1074/jbc.m116.767061
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Sall4 Is Indispensable for Epigenetic Maturation of Mouse Oocytes

Abstract: Sall4 (Splat-like 4) plays important roles in maintaining pluripotency of embryonic stem cells and in various developmental processes. Here, we find that Sall4 is highly expressed in oocytes and early embryos. To investigate the roles of SALL4 in oogenesis, we generated Sall4 maternal specific knock-out mice by using CRISPR/Cas9 system, and we find that the maternal deletion of Sall4 causes developmental arrest of oocytes at germinal vesicle stage with non-surrounded nucleus, and the subsequent meiosis resumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 37 publications
1
38
0
Order By: Relevance
“…What influence does lower H3K4me3 have on the oocyte? In murine oocytes, decreased H3K4me3 level has been linked to misexpression of genes essential for meiotic resumption, leading to failure to maturation (Xu, Chen et al, ; C. Yu et al, ). Consistent with its role in promoting oocyte maturation, increased H3K4me3 was associated with improving meiotic and developmental competence of porcine oocytes (X. X. Yu et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What influence does lower H3K4me3 have on the oocyte? In murine oocytes, decreased H3K4me3 level has been linked to misexpression of genes essential for meiotic resumption, leading to failure to maturation (Xu, Chen et al, ; C. Yu et al, ). Consistent with its role in promoting oocyte maturation, increased H3K4me3 was associated with improving meiotic and developmental competence of porcine oocytes (X. X. Yu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…What influence does lower H3K4me3 have on the oocyte? In murine oocytes, decreased H3K4me3 level has been linked to misexpression of genes essential for meiotic resumption, leading to failure to maturation (Xu, Chen et al, 2017;C. Yu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For example, within the non-correlated cluster 13 TFs were identified which are of putative maternal origin 22 including SALL4. In mice, Sall4 protein is maternally contributed to the zygote, subsequently degraded at 2C and then reexpressed after zygotic transcription has initiated 26 . Consistent with this, SALL4 expression increases dramatically from 8C onwards (Supp.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that histone modifications can regulate the establishment of DNA methylation in the early embryo (Cedar & Bergman, 2009; Hatanaka et al, 2015; Ooi et al, 2007). Aberrant histone modifications can result in impaired oocyte maturation or abnormal embryonic development (Andreu‐Vieyra et al, 2010; Baumann, Viveiros, & De la Fuente, 2010; Hanna et al, 2018; Sha et al, 2018; Xu et al, 2017; Yu et al, 2017). Therefore, epigenetic changes are critical for the acquisition of developmental competence of oocytes.…”
Section: Introductionmentioning
confidence: 99%